Combined effect of hydroxylated and fluorinated acrylate monomers on improving the electro-optical and mechanical performances of PDLC-films. Issue 6 (3rd May 2022) - Hu, Junmei; Hu, Wei; Zhang, Shuaifeng; Sun, Chang; Lan, Ruochen; Cao, Yaping; Ren, Yunxiao; Xu, Jianjun; Wang, Xiao; Saeed, Mohsin Hassan; Jia, Xilai; Yang, Zhou; et al.
ABSTRACT: In this work, we prepared polymer-dispersed liquid crystal (PDLC) films with good mechanical properties, high contrast ratio (CR), and low driving voltage (Vdr ). These PDLC films included two different monomers, which were hydroxyl methacrylate monomers and fluorinated methacrylate monomers. The electro-optical properties, micro-structures and mechanical properties of these films were also characterised. It was found that the hydroxyl methacrylate monomers could improve the adhesion force of the PDLC film, while fluorinated methacrylate monomers could reduce the driving voltage. In this way, the PDLC films with excellent comprehensive performance could be obtained. Compared with the original sample, the adhesion force was improved approximately 200% to 180 N/cm 2 . The driving voltage threshold was reduced about 140% to 18.5 V. The contrast ratio was increased about 150% to 51.9. This work enlightened a novel way to improve the mechanical properties of PDLC films and promised a broader application of PDLC. Graphical Abstract: uf0001